AMBIGUITY IN THE PROFIT-SHARING SYSTEM OF MUDHARABAH COOPERATION FROM THE PERSPECTIVE OF FIQH MUAMALAH (UUM Journal of Legal Studies, 2026)
This study examines the profit-sharing system in cage fish farming cooperation, where farmers are required to bear one-third of the capital in the event of losses. The purpose of this research is to reveal the practice of profit-sharing cooperation among cage fish farmers in Lake Maninjau, Agam Regency, West Sumatra Province, and to identify the risks of losses that occur. This study employs a qualitative approach with a field research design.  In collecting data, researchers conducted interviews with seven informants consisting of one fish cage financier, four fish cage managers, one fish cage owner, and one community leader. The data were analyzed using qualitative descriptive analysis. The findings indicate that profits are divided equally between investors and cage fish managers, with each receiving 50%. However, losses caused by natural factors such as mass fish deaths due to volcanic sulfur (tubo belerang), are charged to the managers, who must bear one third of the capital. The study concludes that the ambiguity in the profit-sharing arrangement leads to injustice for one party. Profit sharing is misunderstood when only profits are shared, while losses due to natural disasters are partially borne by workers. This practice reflects inequity in the mudharabah contract under a profit-sharing system during natural disasters.
Keywords: Cage fish farmers; fiqh muamalah; justice; mudharabah; revenue sharing